Bioremediation of Cadmium (Cd) in Batik Wastewater Using Different Carrier Media Containing Rhizobacteria - Lestari, Sri; Oedjijono, Oedjijono; Santoso, Slamet; Kusharyati, Dyah Fitri; Fathurrohim, Ramadi Habib (Biosaintifika: Journal of Biology & Biology Education, 2023)
Batik wastewater is very dangerous for the environment and health because it contains heavy metals, such as Cadmium (Cd), derived from naphthol and indigo sol dyes. Rhizobacteria have great potential to detoxify Cd on a laboratory scale. Therefore, they should be packaged in carrier media to ensure their long-term viability in the field. The carrier media used were peat, sawdust, and tofu solid waste. This research aimed to determine the most potential of three rhizobacteria as tolerant to Cd from 11 isolates, the best carrier media that can maintain rhizobacteria viability after freeze-dried, and the effectiveness of carrier media containing potential rhizobacteria in reducing Cd in batik wastewater. Furthermore, an experimental method with completely randomized and split-plot designs was used. Rb1, Rb3, and Rb6 were the most Cd-tolerant of the three rhizobacteria isolates tested. For the viability of each isolate, tofu solid waste and peat were the best carrier media at Rb, while sawdust and tofu solid waste were the best at Rb3 and peat at Rb6. Isolate Rb3C3 had the highest percentage value of degrading Cd at 85.1%, while others had less than 80%. Isolate rhizobacteria with a carrier media makes it easy to apply on a field scale because it already contains a source of nutrients for bacterial growth and the packaging has a longer shelf life.